Angular distribution dependence of W migration on the ITER divertor from ERO2.0 simulations - F. Chang; D. Nishijima; M.I. Patino; M.J. Baldwin; J. Romazanov; W. Möller; G.R. Tynan (Nuclear Fusion)
The tungsten (W) surface of the ITER divertor might provide suitable surface temperatures and helium (He) influxes for the formation of microscopic fuzz structures. The change of surface morphology can influence the angular distribution of the sputtered W, and thus might alter the migration of W on the divertor. In this work, the influence of angular distribution of sputtered W atoms on the migration of W in the ITER divertor region has been investigated with ERO2.0 simulations. Using unidirectional angular distributions, it is demonstrated that, while the migration of W ions is restricted by the field lines and thus not sensitive to the angular distribution, the migration of neutral W atoms is determined by the direction of their initial velocity due to the line-of-sight redeposition mechanism. Neutral atom deposition at a location far from the erosion location is suppressed by ionization of atoms. Angular distributions of W sputtered from a flat surface and a fuzzy surface are obtained with TRI3DYN simulations assuming W sputtering by neon (Ne) ions, the energy and angular distributions of which are obtained from a Monte–Carlo simulation of their motions in the magnetic presheath. The flat surface favors sputtering in the forward direction of the incident Ne ions, while the fuzzy surface enhances sputtering in the backward direction. Despite the clear differences in their angular distributions, the deposition profiles from the two surface types are not significantly different because the suppression of neutral atom deposition caused by ionization dominates the deposition profile, resulting in the neutral atom deposition peaking close to the strike points regardless of the angular distributions. The results imply that the angular distribution changes caused by the formation of fuzz on the divertor region might not significantly affect the W migration in the ITER tokamak.